Grapevine Plasticity in Response to an Altered Microclimate: Sauvignon Blanc Modulates Specific Metabolites in Response to Increased Berry Exposure. Issue 3 (1st December 2015) - Young, Philip R.; Eyeghe-Bickong, Hans A.; du Plessis, Kari; Alexandersson, Erik; Jacobson, Dan A.; Coetzee, Zelmari; Deloire, Alain; Vivier, Melané A.
Abstract : Grapevine responds to increased exposure in the bunch zone by up-regulating photoprotective carotenoids in the early developmental stages and volatile terpenoids in the later ripening stages of the berries in a proposed mechanism of antioxidant homeostasis maintenance. Abstract: In this study, the metabolic and physiological impacts of an altered microclimate on quality-associated primary and secondary metabolites in grape ( Vitis vinifera ) 'Sauvignon Blanc' berries was determined in a high-altitude vineyard. The leaf and lateral shoot removal in the bunch zones altered the microclimate by increasing the exposure of the berries. The physical parameters (berry diameter and weight), primary metabolites (sugars and organic acids), as well as bunch temperature and leaf water potential were predominantly not affected by the treatment. The increased exposure led to higher levels of specific carotenoids and volatile terpenoids in the exposed berries, with earlier berry stages reacting distinctly from the later developmental stages. Plastic/nonplastic metabolite responses could be further classified to identify metabolites that were developmentally controlled and/or responded to the treatment in a predictable fashion (assessed over two consecutive vintages). The study demonstrates that grapevine berries exhibit a degree of plasticity within their secondary metabolites and respond physiologically to the increased exposure by increasing metabolites with potential antioxidant activity. Taken together, the data provide evidence that the underlying physiological responses relate to the maintenance of stress pathways by modulating antioxidant molecules in the berries.